Pemodelan Manajemen Pemeliharaan Komponen Arsitektural Gedung Direktorat Politeknik Negeri Semarang - Mohammad Abdul Jalil; Resty Amalia; Marsudi Marsudi; Martono Martono (Politeknik Negeri Semarang, 2014)
Government buildings are buildings used for official purposes. Condition of the building must be taken to ensure that the activities there are running smoothly. One of the solution by doing some maintenance management well. This is related to maintenance activities at the Directorate Building of State Polytechnic of Semarang as one of public universities in Semarang. The purpose of this study is to enhance building maintenance management by arranging modeling Standard Operational Procedure (SOP) for the maintenance and care, especially on architectural components of Directorate Building State Polytechnic of Semarang. Observations on object research, literature study, testing on SOP modeling and interviews are some methods of research to be conducted in this study. All data were analyzed which then bring out some output SOP maintenance modeling component architecture which provides manual book, routine and periodic scheduling maintenance actions, flow charts and also checklists form. Where the manufacturing modeling of SOP will be tested is based on Permen PU No. 24/PRT/M/2008 on the Guidelines of Building Maintenance and Repair and also other related regulations.